Comparison of Channel Estimation Techniques for a Single Carrier System Using Frequency Domain Equalization and a Similar Hiperlan/2-Like OFDM System - Koppler, Alois; Weigel, Robert; Huemer, Mario; Witschnig, Harald (International Workshop on Multi-Carrier Spread Spectrum and Related Topics, 2001)
In this work we compare the performance of a single carrier system with frequency domain equalization (SC/FDE) with an OFDM (Orthogonal Frequency Division Multiplexing) system as described in the Hiperlan/2 and IEEE 802.11a standards. The SC/FDE concept proves to have a couple of similarities to OFDM systems in terms of cyclically extended transmit blocks, frequency domain processing, and more. In our proposed single carrier system [1] as well as in Hiperlan/2-like OFDM systems, an estimation of the channel transfer function is needed for equalization purposes. We present different frequency domain based channel estimation techniques for both applications which are quite comparable. Simulations have been done for channel-coded data in typical indoor multipath environments delivering BER-curves. Our results indicate that the proposed concepts achieve similar bit error rate performances for both systems while efficient channel estimation is by far less complex for the SC/FDE system. Moreover, the analog hardware requirements are much more moderate for the SC/FDE system compared to OFDM systems.
elib2cris::1512001600,koppler2001b
Keywords: Channel Estimation; Single Carrier System; Frequency Domain Equalization; OFDM